Evaluation of drone and ground releases of Cryptolaemus montrouzieri for mealybug (Pseudococcus maritimus) control in apples - Erica Moretti; Rebecca A. Schmidt-Jeffris (Biological Control, 2025)
In apple growing regions of Washington State (USA), mealybug outbreaks are infrequent but can be severe, especially in organic production systems. Because insecticide sprays are ineffective for this pest, management tactics are limited, and alternative approaches that are compatible with organic practices are needed. In four trials (2020–2023), we evaluated releases of mealybug destroyers, Cryptolaemus montrouzieri Mulsant (Coleoptera: Coccinellidae), for the control of grape mealybug, Pseudococcus maritimus (Ehrhorn) (Hemiptera: Pseudococcidae), in commercial organic apple orchards. Although C. montrouzieri are well known for their role in classical biological control of mealybug pests in a variety of cropping systems worldwide, this is the first report of their use as augmentative biocontrol in apple orchards in the US. Different application types (drone vs hand-releases), timings, life stages (adults vs larvae), and rates were tested. In 2020, early season hand releases at high rates (12,355/ha) reduced P. maritimus relative to the untreated control, but in subsequent years no efficacy was observed; pest pressure was also lower in these trials. Across all four years of the study, C. montrouzieri adults dispersed rapidly from field sites, especially in drone releases. Further research is needed to assess if larval releases in mealybug “hot spots” can be effective. Based on their propensity for dispersal, high host-density dependence, and expense, releases of adult C. montrouzieri for P. maritimus control in apple are not strongly supported.